2001
DOI: 10.1021/jp010152w
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Glyoxal Formation from Aromatics:  Experimental Evidence for the Bicycloalkyl−Radical Pathway from Benzene, Toluene, and p-Xylene

Abstract: A new approach is presented to study the ring-cleavage process of benzene, toluene, and p-xylene (BTX). DOAS (differential optical absorption spectroscopy) was used for the simultaneous measurement of the respective ring-retaining products as well as glyoxal (a ring-cleavage product) in a series of experiments at the EUPHORE outdoor simulation chamber, Valencia/Spain. The good time resolution of the DOAS measurements (1-2 min) allowed the primary formation of glyoxal to be separated from any further contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
284
3
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(309 citation statements)
references
References 42 publications
18
284
3
4
Order By: Relevance
“…α-Dicarbonyls showed concentrations ranging from 3.5 to 289 ng m -3 , with an arithmetical average of 51.5 ng m -3 in daytime and 59.8 ng m -3 in nighttime. Glyoxal (Gly) and methylglyoxal (MeGly) are gas-phase oxidation products of numerous VOCs such as benzene, toluene, xylene (Volkamer et al, 2001), ethylene (Ervens et al, 2004), isoprene (Zimmermann and Poppe, 1996) and terpene (Fick et al, 2004), and could act as precursors of secondary organic aerosols via heterogeneous processes (Kroll et al, 2005;Liggio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…α-Dicarbonyls showed concentrations ranging from 3.5 to 289 ng m -3 , with an arithmetical average of 51.5 ng m -3 in daytime and 59.8 ng m -3 in nighttime. Glyoxal (Gly) and methylglyoxal (MeGly) are gas-phase oxidation products of numerous VOCs such as benzene, toluene, xylene (Volkamer et al, 2001), ethylene (Ervens et al, 2004), isoprene (Zimmermann and Poppe, 1996) and terpene (Fick et al, 2004), and could act as precursors of secondary organic aerosols via heterogeneous processes (Kroll et al, 2005;Liggio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Toluene is a major anthropogenic SOA precursor in highly industrialized areas like the Pearl River Delta region (Ding et al, 2012), and it is a precursor to form glyoxal and methylglyoxal (Volkamer et al, 2001;Nishion et al, 2010). From our tunnel study we observed that average mass ratios of glyoxal-to-toluene and methylglyoxal-to-toluene were 0.1 and 0.03, respectively.…”
Section: Emission Estimation For Glyoxal and Methylglyoxalmentioning
confidence: 99%
“…Glyoxal and methylglyoxal can both formed from the oxidation of VOCs (Calvert et al, 2000(Calvert et al, , 2002Volkamer et al, 2001) and emitted directly from tailpipes and biomass burning Kean et al, 2001;Hays et al, 2002;Ban-Weiss et al, 2008), yet direct emissions were viewed as being minor when compared to the secondary formation (Volkamer et al, 2005;Fu et al, 2008). As for speciated carbonyls emitted by gasoline and diesel vehicles, data were mostly obtained from tunnel studies carried out in the United States more than a decade ago Kean et al, 2001;Hays et al, 2002), and the trends in carbonyl emissions from vehicles were thereafter reviewed by Ban-Weiss et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…60±70 ng m -3 ) at night. Glyoxal (Gly) and methylglyoxal (MeGly) are produced by gaseous-phase oxidation from various VOCs including ethylene (Ervens et al, 2004), and toluene, benzene, xylene (Volkamer et al, 2001) as well as terpenes (Fick et al, 2004) and isoprene (Zimmermann and Poppe, 1996). Interestingly, Gly showed higher concentrations in daytime whereas MeGly is more abundant in nighttime (Table 2).…”
Section: α-Dicarbonylsmentioning
confidence: 99%